An Intelligent Trading System with Fuzzy Rules and Fuzzy Capital Management. Issue 8 (11th April 2015) - Naranjo, Rodrigo; Meco, Albert; Arroyo, Javier; Santos, Matilde; Li, Tianrui; Lu, Jie; López, Luis Martínez
<x xml:space="preserve">Abstract</x> In this work, we are proposing a trading system where fuzzy logic is applied not only for defining the trading rules, but also for managing the capital to invest. In fact, two fuzzy decision support systems are developed. The first one uses fuzzy logic to design the trading rules and to apply the stock market technical indicators. The second one enhances this fuzzy trading system adding a fuzzy strategy to manage the capital to trade. Additionally, a new technical market indicator that produces short and long entry signals is introduced. It is based on the moving average convergence divergence indicator. Its parameters have been optimized by genetic algorithms. The proposals are compared to a classical nonfuzzy version of the proposed trading systems and to the buy‐and‐hold strategy. Results favor our fuzzy trading system in the two markets considered, NASDAQ100 and EUROSTOXX. Conclusions suggest that the use of fuzzy logic for capital management is promising and deserves further exploration.